Estimation of default probability for automobile loans - Magboo, Kim Paulo D.
Abstract (This study provides comprehensive default probability estimation for automobile loans. An extension of the Cox Proportional Hazards model proposed by Vaida and Xu (2000) by incorporating random-effects was used to handle clustered survival data. The estimation procedure was used in the context of credit scoring incorporating term of the financial obligation as a cluster-specific random component. Balancing was performed due to the highly imbalance nature of the data. Under-sampling was performed to make the censored class less dominant. The estimated model captured dimensions of automobile loan borrowers such as characteristics and payment behavior. Borrowers tend to exhibit correlation in default incidence within the same loan term, but different propensity to default was observed across loan terms. Models estimated using the balance data exhibit better predictive performance relative to the model estimated using the imbalance data. The final model can be a basis for developing collection strategies and loan loss provision for effective loan management).
June 2018.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Probability estimation